Begonia subvillosa, new running wild Begonia in Cibodas Botanical Gardens and naturalized prediction - Muhammad Efendi; Abidin Ibrahim; Yani Suryani; Salma Salsabila (My University, 2022)
.
Keywords: Begonia; Plant and Fungal Species Descriptions